[S-methyl-11C]-L-methionine positron emission tomography/computed tomography imaging parameters to evaluate early response for esophageal cancer with neoadjuvant carbon ion radiotherapy - Kazuo Narushima; Ryuichi Nishii; Shinichi Okazumi; Hideaki Shimada; Yasunori Akutsu; Takamasa Maeda; Shigeo Yasuda; Shigeru Yamada; Kiyohiko Shuto; Kentaro Tamura; Kana Yamazaki; Makoto Shinoto; et al. (Scientific Reports, 2022)
Abstract This study aimed to evaluate the uptake of the clinical effectiveness of [S-methyl-11C]-L-methionine positron emission tomography/computed tomography (MET PET/CT) in patients with esophageal cancer and to investigate MET PET/CT imaging parameters to assess early response for esophageal cancer with neoadjuvant carbon ion radiotherapy (CIRT). MET PET/CT scans were performed in nineteen patients before and 3 weeks after completion of CIRT. After Surgery, the effect of neoadjuvant CIRT was investigated by examining the relationship between each parameter of MET uptake and the histological assessment (grade and tumor residual ratio). Four parameters of MET uptake were the maximum and minimum standardized uptake values of pre and post CIRT (pre-SUVmax, pre-SUVmean, post-SUVmax, and post-SUVmean). MET PET/CT imaging of esophageal cancer was clearly demonstrated. The post-SUVmax was the most suitable parameter. When the cutoff value was set as post-SUVmax = 6.21, the sensitivity, the specificity, and the accuracy of Grades 3 were 100.0%, 63.6%, and 78.9%, respectively. And there was a positive relationship between the tumor residual ratio and post-SUVmax (R 2  = 0.38, p < 0.005). MET PET/CT is clinically useful for the assessment of early response to neoadjuvant CIRT in esophageal cancer. Particularly, post-SUVmax is considered a promising PET imaging parameter.